Personalized Medicine of Monoclonal Antibodies in Inflammatory Bowel Disease: Pharmacogenetics, Therapeutic Drug Monitoring, and Beyond - Di Paolo, Antonello; Luci, Giacomo (Frontiers in Pharmacology, 2021)
The pharmacotherapy of inflammatory bowel diseases (Chron’s disease and ulcerative colitis) has experienced a significant progress with the advent of monoclonal antibodies (mABs). As therapeutic proteins, mABs display peculiar pharmacokinetic characteristics that differentiate them from chemical drugs, as aminosalicylates, antimetabolites (i.e., thiopurines and methotrexate) and immunosuppressants (corticosteroids and cyclosporine). However, clinical trials have demonstrated that biologic agents may suffer from a pharmacokinetic variability that could influence the desired clinical outcome, beyond primary resistance phenomena. Therefore, therapeutic drug monitoring (TDM) protocols have been elaborated and applied to adaptation drug doses according to the desired plasma concentrations of mABs. This activity is aimed at maximizing the beneficial effects of mABs while sparing patients from toxicities. However, some aspects of TDM are still under discussion, as well as the time-changing therapeutic ranges, the proactive and reactive approaches, the performance and availability of instrumental platforms, the widely varying individual characteristics of patients, the severity of the disease and the coadministration of immunomodulatory drugs. Facing these issues, the personalized medicine in IBD may take advantage from a combined approach, made by TDM protocols and pharmacogenetic analyses in a timeline that necessarily considers the frailty of patients, the chronic administration of drugs, the possible worsening of the disease. Therefore, the present review present and discuss the activities of TDM protocols of mABs on the light of most recent results, with a special attention for the integration with other actions aimed at exploiting the most effective and safer therapeutic effects of drugs prescribed in IBD patients.